MANAGEMENT LEADERSHIP IN OFFICER TRAINING - Soyibnazarov Ulugbek Shonazarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Today, the military practice requires an officer-manager who is focused on democratic managerial priorities in the “man-to-man” system, capable of updating and self-development of his managerial knowledge and skills, able to independently navigate the changing social and military reality, adequately assessing it, accepting thoughtful, rational decisions, owning modern tactics and strategies for managing military teams.